Lectura Dantis - Mandelbaum, Allen,Ross, Charles Stanley (University of California Press, 1999)
The California Lectura Dantis is the long-awaited companion to the three-volume verse translation by Allen Mandelbaum of Dante's Divine Comedy. Mandelbaum's translation, with facing original text and with illustrations by Barry Moser, has been praised by Robert Fagles as
Description based on publisher supplied metadata and other sources